Language Variation in Alternate Universe (AU) on Social Media: A Sociolinguistic Study - Rofi Atin Khanifah; Suhartono Suhartono; Agusniar Dian Savitri (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study aims to examine linguistic variations in Alternate Universe (AU) content on the platforms X, TikTok, and Instagram, and to analyze their relationship with reader interests. AU, as a form of cyberliterature, has flourished on social media and employs informal language that reflects digital communication practices. This study employed a descriptive qualitative approach, utilizing linguistic units (words, phrases, clauses, and sentences) containing linguistic variation in AU content across the three platforms. The data were also garnered from questionnaire data from the AU reader community. Data were analysed using William Labov’s theory of linguistic variation. The results showed that the identified language variations included vulgar language, slang, and code-mixing, which were used systematically and contextually. There are different tendencies of how language variation occurred across platforms. Platform X tends to use vulgar language more explicitly to heighten emotional expression and narrative conflict. TikTok demonstrates a predominance of concise and efficient slang, while Instagram features a mix of code-switching and more context-specific slang as a strategy for expression and communicative aesthetics. The research findings also indicate that the use of language variations aligned with platform characteristics correlates with increased reader interest, as evidenced by positive responses to language perceived as communicative, relatable, and relevant to everyday communication practices. Theoretically, this study reinforces sociolinguistic research on language variation as a phenomenon influenced by social context, and it extends the inquiry into the digital realm by demonstrating how social media platforms help shape language variation. This study contributes to the development of digital sociolinguistic research, particularly in understanding the dynamics of language in social media-based narratives.